An ecologically and socially inclusive model of agritourism to support smallholder livelihoods in the South Pacific. Issue 3 (4th March 2017) - Addinsall, Cherise; Scherrer, Pascal; Weiler, Betty; Glencross, Kevin
ABSTRACT: The neglect and marginalisation of smallholders in economic and development policy contributes to increasing vulnerability of rural communities. Underinvestment in agriculture, climate change impacts and growing competition for land and water places further pressure on smallholders. In this context, this paper examines the current focus in the South Pacific on strengthening the linkages between tourism and agriculture through agritourism. The paper seeks to merge multiple discourses, by firstly reviewing the development model that is driving tourism and linkages to agriculture in the South Pacific. Secondly, agritourism as it is conceptualised in the tourism literature and thirdly sustainable tourism discourse, to identify economic activities within agritourism that contribute to enhancing smallholders' livelihoods in the South Pacific. An ecologically and socially inclusive model of agritourism is put forward based on principles of sustainable tourism and agroecology – referred to as agroecological tourism. Agroecological tourism strengthens the linkages between tourism and agriculture while fostering sustainability principles.